2008
DOI: 10.15353/joci.v4i3.2946
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks and Social Capital: Rethinking Theory in Community Informatics

Abstract: One important theoretical focus in community informatics is based on the convergence of two established bodies of theory, social networks and social capital. First we summarize them both. Then we define community informatics and explore its origins. Finally, we review a group of community informatics studies which frame their analyses in either social capital or social network theory. How the frames are constructed focuses each study on either technological change or historical continuity. Taken together, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(27 citation statements)
references
References 60 publications
0
25
0
2
Order By: Relevance
“…SNT argues that organisations should not be studied in isolation because they are ultimately influenced by the network to which they belong to (Williams and Durrance, 2008). Key SNT principles include graph hierarchy, graph efficiency, least upper boundedness, centralisation index, density, clique, n-cliques, clique overlap, clique multiplexity, simmelian ties, homophily, multiplexity, heterophily, structural holes, strength of ties, strength of weak ties, weak ties, influence, propinquity, mutuality (reciprocity or symmetry), distance, "small world", degree of connectedness, embeddedness and transitivity (Scott, 2000, p. 7).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…SNT argues that organisations should not be studied in isolation because they are ultimately influenced by the network to which they belong to (Williams and Durrance, 2008). Key SNT principles include graph hierarchy, graph efficiency, least upper boundedness, centralisation index, density, clique, n-cliques, clique overlap, clique multiplexity, simmelian ties, homophily, multiplexity, heterophily, structural holes, strength of ties, strength of weak ties, weak ties, influence, propinquity, mutuality (reciprocity or symmetry), distance, "small world", degree of connectedness, embeddedness and transitivity (Scott, 2000, p. 7).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Research and community initiatives that aim to address underserved areas are being brought together under the name community informatics (Bishop & Bruce, 2005;de Moor, 2009;Gurstein, 2000;Keeble & Loader, 2001;Williams & Durrance, 2008; see the Journal of Community Informatics, http://ci-journal.net/). Community informatics includes deliberate interventions that strive to make a difference in the lives of people living in regions of low-income or low-Internet accessibility (e.g., Hampton, 2010 [this issue]) or for those who tend to be underserved in society and are thus often late to adopt contemporary work and information practices (e.g., older or rural community members; Commission of the European Communities, 2005).…”
Section: Working With Communitiesmentioning
confidence: 99%
“…Community informatics includes deliberate interventions that strive to make a difference in the lives of people living in regions of low-income or low-Internet accessibility (e.g., Hampton, 2010 [this issue]) or for those who tend to be underserved in society and are thus often late to adopt contemporary work and information practices (e.g., older or rural community members; Commission of the European Communities, 2005). Theoretical underpinnings for this work often derive from the ideas of social capital-that is, how the social network of interactions, obligations, trust, and reciprocity among a set of actors create an accessible set of resources for individual and communal support (Kavanaugh & Patterson, 2002;Lin, 2001;Mesch & Talmud, 2010 [this issue];Pigg & Crank, 2004;Putnam, 2000;Williams & Durrance 2008).…”
Section: Working With Communitiesmentioning
confidence: 99%
“…Social assets had been declared as a result of a process of social and economic organization such as trust, reciprocity, informational and economic exchange, formal and informal group's activities. Improving social assets condition in the community will improve collective action, as well as social and economic condition (Williams & Durrance, 2008). Stone (2003) defined social asset as the extent and nature of relationships people have with others, the relationships people have with their communities, and relationships between people and various services, institutions and systems.…”
Section: Introductionmentioning
confidence: 99%
“…It is also a concept that can be used to understand the linkages between communities or institutions that will increase social collaboration through coordination and cooperation to reach social goals. A research by Williams and Durrance (2008) showed that agriculture sectors has been linked to social asset using indicators, such as network and membership (where the people link to) and social trust (how member organization can trust each other) (Gayatri, Sumarjono, & Satmoko, 2018).…”
Section: Introductionmentioning
confidence: 99%